Validation of meteorological and ground-level ozone WRF-CHIMERE simulations in a mountainous grapevine growing area for phytotoxic risk assessment - Blanco-Ward, Daniel (2018)
Ozone is the most damaging phytotoxic air pollutant to crop yield quantity and quality. This study presents the validation of a simulation with the WRF-CHIMERE modelling system in order to assess the risk of phytotoxicity by tropospheric ozone for an important and characteristic Mediterranean crop, i.e. the grapevine. The study region was the Douro wine region in Portugal, which is characterized by a rugged relief and a Mediterranean climate. The simulation covered a reference grapevine growing season in the Northern Hemisphere (from April to September 2017), during which a particular measuring campaign was also carried out. The validation of the meteorological simulations on a daily and hourly time resolution was performed based on data from three weather stations, namely on temperature, global solar radiation, relative humidity, wind speed and direction values. The ozone phytotoxicity was assessed with data from two measuring stations. A specific grapevine growth parameter based on monitored phenological observations was introduced for ozone stomatal uptake assessment. Concerning meteorology, validation statistics were acceptable and within the range of what has been found in other regional climate modelling simulations. Ground-level ozone-based values were calculated for a better assessment of the phytotoxic risk, in particular cumulative standards for vegetation protection. Stomatal flux estimates were within the range of those measured for the local cultivars in the field campaign when there was not severe water stress limitation. Both field and statistically adjusted model values indicate that considerable areas in the Demarcated Douro Region of Portugal can exceed the critical exposure values for vegetation according to current European legislation standards. Moreover, measured and simulated results indicate an ozone impact on grapevine yield and quality in the target region because the exposure- and flux-based indices exceed the criteria based on current open-top-chamber experimental knowledge.